The impact of financial education for youth in Ghana - Dean Karlan; James Berry; Menno Pradhan (Yale University, Economic Growth Center, 2015)
We evaluate, using a randomized trial, two school-based financial literacy education programs in government-run primary and junior high schools in Ghana. One program integrated financial and social education, whereas the second program only offered financial education. Both programs included a voluntary after-school savings club that provided students with a locked money box. After nine months, both programs had significant impacts on savings behavior relative to the control group, mostly because children moved savings from home to school. We observed few other impacts. We do find that financial education, when not accompanied by social education, led children to work more compared to the control group, whereas no such effect is found for the integrated curriculum; however, the difference between the two treatment effects on child labor is not statistically significant.
Keywords: D14; J22; J24; O12; 330; financial literacy; youth finance; savings